Artificial Intelligence in Forensic Sciences Revolution or Invasion? Part II - Márton Lontai; Horolma Pamjav; Dávid Petrétei (Belügyi Szemle, 2024)
Aim: The study is on the emerging role of artificial intelligence in the forensic sciences. After clarifying the basic concepts and a brief historical overview, the possibilities of using AI in various forensic fields are discussed: genetics, pattern recognition, chemistry, toxicology, anthropology, forensic medicine, and scene reconstruction.